Accelerometer measures of field hockey skills development - Tremayne, M.; Thiel, D. V.; Nottle, S. (Sports Technology, 2011)
Stick speed and ball control are essential skills in field hockey but few training drills provide a quantitative measure of skill. In this study, skill development was quantified in junior elite hockey players using stick-mounted accelerometers to record hit events and the timing between each hit. Two state-ranked female groups (Under 15 and Under 18) performed four drills twice. Between the first and the repeat test, the Under 18 team experienced intense training for 3 weeks while the Under 15 team did routine weekly training for over 6 weeks. Up to 22% team improvement was evident between the training sessions. The speed of ball delivery for reverse-stick drills requiring control of the ball direction was much lower (p < 0.01) than similar forehand drills. Both teams showed little or no improvement in the reverse-stick drills. The results suggest that the modified Chapman ball control test is a good measure of stick speed and ball control. The more experienced players had much higher Chapman scores, and hit times were significantly faster (p < 0.01) than that recorded in the other drills. This low-cost measurement technique allows coaches to monitor youth training and skills improvement in field-based exercises without the use of video.